The Relationship Between Corporate Social Responsibility (CSR) and FINANCIAL PERFORmance in a Company - Romadhon, Moch Iqbal; Putri, Nabila Amelia; Hwihanus, Hwihanus (Business and Investment Review, 2024)
Corporate financial performance, or CFP, and corporate social responsibility are linked concepts. CSR enhances employee productivity and fosters collaboration among peers. Financial performance and corporate social responsibility have a favorable correlation. Depending on whether there was a good or negative association between CSR and financial success, we may draw conclusions from our investigation's findings. We selected, aggregated, perused five papers titled "CSR relationship with financial performance from different countries," and conducted tests on several samples. A type of corporate social responsibility for their commercial endeavors is called CSR. An association called CSR exists for businesses that put their CSR systems into place. By using CSR, businesses may set themselves apart from their rivals. Although not all businesses in the globe use or even adopt CSR for their commercial operations, corporations nowadays will understand how crucial it is for a company. The study's conclusions indicate that corporate social responsibility, or CSR, improves a business's bottom line. Companies that participate in CSR get more revenue and assets. However, other studies contend that there is no positive relationship between a business's profitability and its commitment to corporate social responsibility. Future researchers can use this study's methodology to evaluate the connection between a business's financial performance and corporate social responsibility (CSR).